Rural and Urban Land and Building Tax Fines and Taxpayer Compliance: A Constitutional Law Review and Its Relevance to Local Revenue - Darmawan, Didit; Rizky, Muchammad Catur; Khoirunnisah, Nailah Bintang; Nadhira, Adellia Putri (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2025)
Rural and Urban Land and Building Tax (PBB-P2) is a major source of Local Own-Source Revenue (Pendapatan Asli Daerah, PAD) in Indonesia and is administered by local governments within the country’s delegative decentralization framework. While local fiscal autonomy enables regions to adjust certain parameters of PBB-P2 administration through local regulations, the use of sanctions, particularly fines for late payment or non-compliance,raises a constitutional question regarding the limits of regional taxing authority and the protection of taxpayers’ rights. This study addresses the gap between fiscal-administrative discussions of PBB-P2 enforcement and a constitutional law assessment of whether local fine regimes remain legitimate under rule-of-law standards. This research employs a normative-juridical (doctrinal) approach by analyzing applicable positive law governing local taxation, especially Law No. 28 of 2009 on Regional Taxes and Regional Levies alongside relevant administrative practices oncerning PBB-P2 fines and arrears. The analysis demonstrates that local governments are constitutionally permitted to impose PBB-P2 fines as part of fiscal decentralization and regional autonomy; however, such authority is not absolute. Because fines directly impose coercive burdens in the state–citizen relationship, their design and enforcement must comply with the principles of legality and legal certainty, proportionality, and non-discrimination. These requirements demand clear and accessible standards for liability, predictable calculation and collection procedures, reasonable calibration between the fine and the taxpayer’s conduct (including realistic ability to comply), and equal treatment for similarly situated taxpayers, supported by fair procedures and effective remedies. The study concludes that strengthening PBB-P2 enforcement should not rely solely on deterrence logic or revenue targets. Evidence-based improvements are needed to align sanction design with constitutional safeguards, thereby enhancing compliance while sustaining public trust and the legitimacy of local taxation.